Inmigrants from a country of the european union: Romanian inmigrants´social network, irregular inmigration and access to the labour market - Pajares, Miguel (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Romanian immigration to Spain has been high in number and has taken place in a relatively short period of time, during which it has become the third most important immigrant group in statistical terms. The reasons behind this phenomenon stem from the living conditions in Romania as well as the particular characteristics of the Spanish labor market in recent years. It should be noted,however, that a side from these factors, it is the strong social network that has truly made possible such an intense migration dynamic.The social network constructed by the Romanians has some unique characteristics: there are few inner relationships, limited primarily to close family and friends, and it is weak in some aspects(except in the case of those belonging to religious minorities and the Roma people). Nonetheless, it is a useful network for labor insertion.Access to the labor market is produced via the «network»to the extent to which Romanians bring others into businesses or make initial contacts for them. In case studies, it has been observed that those Romanians arriving without a social network have a hard time finding work. The primary reason for this is that Romanian immigration has been channeled primarily through illegal means, thus initially entering the labour market in the submerged economy.Since January 1, 2007, the date marking the entry of Romaniain to the European Union, the Romanian community is the contingency with one of the highest rates of irregular immigration. Upon gaining recognition as EU community members, those immigrants who had previously found themselves in an irregular legal situation have been experiencing a change contradictory to their true legal status.